(3TQM GdefXheI GdJdeSGfjIs - (3CHh GdMSf Ydj Hf jMji Hf eMeO Hf UGdM GdYUfhfj GdeZjdj, GdYUfhfjs
(3ChdgG (B:s
(3GdMeO ddg Pi GdLhO hGdcQe GdeajV Ydi YHGOg ShGHZ GdfYe GdefYe HaUGMI GddSGf hJhUjd GdeYGfi ef HYV dHYV HGdbde s
(3BNQgG (B:s
(3Je GdTQM GdeHGQc HMeO Gddgq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdefXheI HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Yde GdaQGFVs